Impact of Using Artificial Intelligence in business modeling - Ida Hindarsah (Journal of Economics and Business (JECOMBI), 2023)
The rapid growth of AI technology has changed the global business landscape, including with various applications such as data analysis, market prediction, and business process automation. This research aims to investigate the impact of using artificial intelligence (AI) in business modeling. This research methodology includes literature analysis to understand the latest trends and developments in the use of artificial intelligence in the business sector with a qualitative approach. The results of this research show that the use of artificial intelligence (AI) in business modeling in Indonesia has a significant positive impact. AI integration increases operational efficiency, optimizes supply chain management, and opens up innovation opportunities. AI also plays an important role in improving corporate security by proactively detecting and responding to cyber threats. Although it requires an initial investment, the long-term benefits include reduced operational costs and competitive advantage. Companies' success in adopting AI can create industry leaders who are able to adapt quickly and use data effectively, helping them face the challenges of an increasingly digital and dynamic future.